A new species of Monstrilla (Copepoda, Monstrilloida) in coastal waters of northern South China Sea - Zhiqian Zhou; Xiping Lian; Yehui Tan (ZooKeys)
A new monstrilloid copepod species, Monstrilla pseudograndis sp. nov., from coastal waters in the northern South China Sea is described and illustrated. The diagnostic characters of this new species include the presence of small setae and sensilla on the forehead and four pairs of nipple-like scars on the ventral surface of the cephalothorax. Although the new species closely resembles Monstrilla grandis Giesbrecht, 1891 in overall morphology, it can be distinguished by the shorter antennule, the thumb-like process on the fifth leg, and the distinctive shape of the oral papilla. This represents the eighth record of this genus from China seas.